Dynamic Linkages between Export and Growth: Does Exchange Rate Volatility Matter? - Zainal, Zalina; Sarmidi, Tamat; Mohd Nor, Abu Hassan Shaari (2016)
This study aims to analyze the dynamics relationship between exchange rates and economic growth in four ASEAN countries; Malaysia, Indonesia, Singapore and Thailand. The study focuses on the effect of exchange rate volatility on growth through trade channels by investigating the effect of interaction between exchange rate volatility and export. Quarterly data from 1984 to 2013 together with two exchange rate volatility series i.e. conditional and non-conditional is generated from exponential generalized autoregressive conditional heteroskedasticity (EGARCH) model and moving average of standard deviation are used. The relationship is estimated using dynamic ordinary least squares method (DOLS) of Stock and Watson (1993). The results suggest that the exchange rate volatility does affect economic growth in all ASEAN countries through international trade. Interestingly, the study found that the positive effect of export is capable in changing the direction of the relationship especially for countries that are able to reduce the negative impact of exchange rates volatility through diversification of trade policy.